2005
DOI: 10.1111/j.0013-9580.2005.55204.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Metabolic Investigation of Topiramate Disposition in Healthy Subjects in the Absence and in the Presence of Enzyme Induction by Carbamazepine

Abstract: Summary:Purpose: To characterize the metabolic profile of topiramate (TPM) in humans and to assess the influence of enzyme induction by carbamazepine (CBZ) on the pharmacokinetics and metabolic profile of TPM.Methods: Twelve healthy subjects received a single oral dose of TPM (200 mg) on two randomized occasions. On one occasion, TPM was administered alone, and on the other, it was given on day 18 of a 24-day treatment with CBZ (maintenance dosage, 600 mg/day). Blood and urine samples were collected for ≥72 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 24 publications
4
44
2
1
Order By: Relevance
“…21,23) Enzyme induction by carbamazepine is associated with an approximately 2 to 3-fold increase in topiramate metabolic clearance. 7,10,22,24) It is interesting to note that in some studies in patients taking carbamazepine, topiramate renal clearance was also found to be significantly increased. 10,22) In contrast to carbamazepine, drug interaction with phenobarbital is considered as minor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,23) Enzyme induction by carbamazepine is associated with an approximately 2 to 3-fold increase in topiramate metabolic clearance. 7,10,22,24) It is interesting to note that in some studies in patients taking carbamazepine, topiramate renal clearance was also found to be significantly increased. 10,22) In contrast to carbamazepine, drug interaction with phenobarbital is considered as minor.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,10,[20][21][22][23][24] Carbamazepine significantly reduces topiramate concentration-to-dose ratio compared to topiramate monotherapy in both children and adults. 21,23) Enzyme induction by carbamazepine is associated with an approximately 2 to 3-fold increase in topiramate metabolic clearance.…”
Section: Discussionmentioning
confidence: 99%
“…References for drugs whose half-lives are altered in patients receiving liver enzyme inducers: felbamate [36], lamotrigine [37], oxcarbazepine [38], rufinamide [39], tiagabine [40], topiramate [41] and zonisamide [15]. b Half-life increases to 30–90 h during concomitant therapy with valproic acid (enzyme inhibitor).…”
Section: The Challenge Of Establishing Reference Ranges For Aedsmentioning
confidence: 99%
“…Approximately 50% of the absorbed dose is metabolized by the liver, with an increase in metabolism seen in patients concomitantly receiving therapy with classic enzyme inducers. Enzyme inducers can decrease the serum half-life from 20–30 h to approximately 12 h [41,164]. Children generally eliminate topiramate faster than adults [14,165].…”
Section: Topiramatementioning
confidence: 99%
“…Approximately 50% of the absorbed dose is metabolized by the liver. Hepatic enzyme inducers can decrease the serum half-life of topiramate from 20-30 hr to approximately 12 hr (Britzi et al, 2005;Sachdeo et al, 1996). Children generally eliminate topiramate faster than adults (Perucca, 2006;Rosenfeld et al, 1999).…”
Section: Topiramatementioning
confidence: 99%